The Evaluation of Drug Management and Improvement Strategies Using the Hanlon Method in the Pharmacy Installation of the Bahteramas Hospital Southeast Sulawesi - Suherman, Sri Devi Nur Rahma; RA Oetari; Saptarini, Opstaria (Formosa Journal of Multidisciplinary Research, 2024)
Drug management is a drug management cycle which includes these stages as follows: selection, procurement, distribution and use. Ineffectiveness and inefficiency may negatively impact hospitals both medically and economically. This study aims to evaluate drug management in the selection, procurement, distribution and use of drugs at the Bahteramas Hospital, Southeast Sulawesi, with Hanlon method as strategic improvement. This study has done with a descriptive method with data collected retrospectively in 2022 and prospectively, both primary (management record) and secondary (interviews). Results of this study about drug management showed there were 4 indicators that do not comply with standards. Meanwhile, other 10 indicators could comply with the standards. The improvement strategy using the Hanlon method in drug management is to prioritize repairing problems sequentially starting from the average percentage of drug waiting time, suitability of the national formulary and hospital formulary, as well as the percentage of dead stock.